Clinical and Psychosocial Characteristics of Adult Primary Care IBS Patients: A Post hoc Analysis of the DOMINO Study - Robbe Wils; Bert Broeders; Karen Van den Houte; Jan Tack; Florencia Carbone (United European Gastroenterology Journal, 2026)
ABSTRACT Background The majority of irritable bowel syndrome (IBS) patients are diagnosed and managed in primary care, but this setting is underinvestigated to date. Objective The present study aimed to improve our understanding of IBS in primary care by evaluating the clinical and psychosocial characteristics of affected patients. Methods We performed a cross‐sectional post hoc analysis of the DOMINO study, which enrolled 483 adult IBS patients newly diagnosed by primary care physicians. We investigated baseline demographics and questionnaires assessing Rome IV criteria and stool pattern subtype, symptom severity (IBS‐SSS), quality of life (IBS‐QoL), somatic symptom disorder (PHQ‐12), depression (PHQ‐9) and anxiety (GAD‐7). Results 70% of the primary care diagnosed IBS patients fulfilled the Rome IV criteria (Rome+). The stool pattern subtype distribution according to the Rome IV diagnostic questionnaire was: 20% constipation (IBS‐C), 33% diarrhea (IBS‐D), 31% mixed (IBS‐M) and 16% unclassified (IBS‐U). Mean IBS‐SSS was 268 ± 98, with 46% and 36% of cases reporting moderate and severe IBS‐SSS, respectively. Rome + patients had, compared to Rome−, a significantly higher IBS‐SSS, lower quality of life and higher psychosocial comorbidity. IBS‐M, IBS‐D and IBS‐C participants scored significantly higher on IBS‐SSS and IBS‐QoL than IBS‐U. Furthermore, IBS‐M had significantly higher somatic symptom disorder and depression and anxiety levels compared with IBS‐U. Conclusion The majority of primary care IBS patients fulfilled the Rome IV criteria, were subtyped as IBS‐D or IBS‐M and were characterised by moderate or severe IBS‐SSS. Rome+ and IBS‐M participants had higher symptom severity, lower quality of life and higher psychosocial comorbidity. ClinicalTrials.gov , Number NCT04270487.